2010
DOI: 10.1111/j.1556-4797.2010.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Health, Well‐being, and Social Context of Samoan Migrant Populations

Abstract: A minimal estimate suggests 300,000 Samoans reside outside the Samoan archipelago in the United States, New Zealand, and Australia. Anthropological studies of Samoan migration provide a broader perspective that emphasizes the deep connections among individuals and families residing in and outside the Samoas, and the adaptive nature of these connections. A review of the published socioeconomic, demographic, public health, and medical literatures indicates that Samoans residing outside the Samoas may be at high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Henceforth, this population will be referred to as Samoans. Samoans are more susceptible to poor levels of population health as a result of various determinants underpinning their attitudes, access and knowledge of health care, such as socio-cultural issues, low socio-economic status and low health literacy ( 6 , 7 ) . Consequently, Samoans suffer disproportionate rates of non-communicable diseases and avoidable hospital admissions ( 7 – 9 ) .…”
mentioning
confidence: 99%
“…Henceforth, this population will be referred to as Samoans. Samoans are more susceptible to poor levels of population health as a result of various determinants underpinning their attitudes, access and knowledge of health care, such as socio-cultural issues, low socio-economic status and low health literacy ( 6 , 7 ) . Consequently, Samoans suffer disproportionate rates of non-communicable diseases and avoidable hospital admissions ( 7 – 9 ) .…”
mentioning
confidence: 99%
“…This issue is not just confined to this small island territory, Polynesians are the fastest growing population group in the US and there are large communities in Australia, New Zealand and other nations worldwide who also display highly prevalent obesity traits . The level of adult obesity seen in American Samoa in women of childbearing age, a probable contributor to infant obesity, is likely to foreshadow the experience of other developing countries as they undergo similar economic, demographic and nutritional transition to that experienced in American Samoa.…”
Section: Discussionmentioning
confidence: 99%
“…Such analysis may also elucidate biopsychosocial aspects of individual exposure to socio-economic change and cardiovascular disease risk underlying previously observed ecological differences in psychosocial arousal (Bergey et al, 2010) that persisted after adjustment for the individual-level differences observed in the present analysis. Finally, economic development, migration, emigrant remittances to aiga and matai , and changing opportunities for social, political, and economic advancement within villages continue to occur in Samoa and American Samoa and among Samoan communities outside of the archipelago (Macpherson and Macpherson, 2009; McGarvey and Seiden, 2010). Further research on stress and health in the Samoas, and elsewhere, must consider and attempt to assess the historical and socio-cultural context of these dynamic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Chiefs are typically male and their title represents the highest social rank - a rank that symbolizes maturity and prestige, or mamalu (Pitt, 1970). Despite substantial emigration, the aiga and village remain important influences to those residing in other parts of Samoa or abroad, resulting in substantial migrant remittances, active involvement in social and political life, and feelings of connectedness (Ahlberg, 1995; Lilomaiava-Doktor, 2009; Macpherson and Macpherson, 2000; Macpherson and Macpherson, 2009, McGarvey and Seiden, 2010). …”
Section: Introductionmentioning
confidence: 99%